Emotional intelligence and attachment in adulthood: A meta-analysis. (January 2022) - Walker, Sarah A.; Double, Kit S.; Kunst, Hannah; Zhang, Michael; MacCann, Carolyn
Abstract: Attachment styles form during childhood emotional experiences. These experiences may be shaped by emotion-related traits such as how children interpret and regulate their own and others' emotions. These emotion-related traits appear in many emotional intelligence (EI) models, such that EI may relate to attachment styles. We conduct a meta-analysis to estimate the association between EI and attachment styles (26 studies, N = 6914). We include only non-clinical adult samples and validated psychometric assessments. We examine EI type as a moderator, comparing ability EI versus EI rating-scales using subgroups analysis and meta-regression. We find that lower anxious attachment is significantly associated with EI rating-scales ( r = −0.25, k = 26) and ability EI ( r = −0.16, k = 45), lower avoidant attachment is significantly associated with EI rating-scales ( r = −0.36, k = 21) and ability EI ( r = −0.21, k = 40), but secure attachment is significantly associated with EI rating-scales only ( r = 0.31, k = 30). EI type significantly moderated the EI/avoidant attachment association only (β = −0.14, p = .01). We discuss possible mechanisms by which EI could influence early development of attachment styles (and vice-versa) while acknowledging that the causal direction underlying EI/attachment associations is unclear.